Application of Earth Remote Sensing Data in Land use and Management in Cartography - G. A., Artikov; F. M, Tozhidinova (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the innovative aspects of aerospace monitoring for cadastral work and analyses the issues of monitoring in the cadastral automation system associated with the processing of information on cadastral objects. Aerospace monitoring methods are also used in cadastral surveys. The photographs allow to determine the boundaries of the territories and to take into account the property. The basic principles of modern remote sensing in cartography and their application in the creation of maps are listed. Innovative programs for conducting satellite monitoring with other countries are considered